An Assessment of Cross-country Fiscal Consolidation - Bruno Carrasco; Seung Mo Choi (Asian Development Bank (ADB), 2006)
"This paper analyzes fiscal adjustment by reviewing the cross-country experience of the Organization for Economic Cooperation and Development (OECD) or mature economies, and the emerging market economies during 1970-2002. We find that initial conditions, composition, and timing of adjustment matter for successful fiscal adjustment (SFA). First, countries with higher primary deficits and larger government debts are more likely to pursue SFA. Second, in mature economies, SFA is driven by expenditure compression measures (largely cutbacks in subsidies) rather than by revenue augmentation measures. On the other hand, in emerging market economies, while expenditure compression measures (in particular, a decrease in capital expenditure) drive SFA, revenue augmentation measures also play an important role. Third, synchronizing fiscal adjustment to an expansionary phase of the business cycle increases the likelihood of its success. A probit analysis tends to support these findings. Finally, we review whether fiscal adjustment can indeed be expansionary. The findings point to a weak inclination toward noncontractionary outcomes, although further research is required to explain what drives this non-Keynesian result."
hdl:11540/1873
Keywords: 330; Finanzverwaltung; Anpassung; Öffentliche Finanzen; OECD-Staaten